Training today's people better employees through gaming - Edery, David 1976- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Changing the game: how video games are transforming the future of business (ISBN: 9780132357814) by David Edery and Ethan Mollick. Learn how powerful and cost-effective new video game technologies can supercharge business training, reaching a new generation of learners more effectively than any other approach. Games can improve employees' abilities to work in teams, use systems thinking, and learn from virtual experience when real experience is too costly or difficult"--Resource description page.